2024
DOI: 10.3390/foods13111608
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food Waste Compost, Vermicompost, and Chemical Fertilizers on the Growth Measurement of Red Radish (Raphanus sativus): A Sustainability Perspective in the United Arab Emirates

Sara B. Almaramah,
Abdelghafar M. Abu-Elsaoud,
Wejdan A. Alteneiji
et al.

Abstract: The pressing need for sustainable agricultural practices, especially with the increasing population, has directed attention towards alternative fertilizers that enhance crop yield while preserving soil integrity and reducing food loss. The current study investigated the comparative efficacy of food waste compost (FOWC), vermicompost, and chemical fertilizers on the growth of red radish. The present work used a systematic experimental design to evaluate plant growth parameters, including radish weight and heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…This present study offers valuable insights into agricultural practices, particularly for enhancing the fresh weight of red radish plants through strategic fertilizer use. The strong association between fertilizer types and fresh and dry weight outcomes suggests potential avenues for manipulating plant growth characteristics through targeted fertilization strategies [38,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This present study offers valuable insights into agricultural practices, particularly for enhancing the fresh weight of red radish plants through strategic fertilizer use. The strong association between fertilizer types and fresh and dry weight outcomes suggests potential avenues for manipulating plant growth characteristics through targeted fertilization strategies [38,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, certain studies have indicated that these compounds are accountable for the chelating characteristics of SCGs, thereby rendering their removal inadvisable. Research has also investigated the utilization of SCGs as bio-chelates, resulting in a combination of waste material and micronutrients that can be used to enhance the nutritional value of edible plants through biofortification [7,8,37,41,42].…”
Section: Discussionmentioning
confidence: 99%